Factors determining job satisfaction of employees at money services business in Malaysia - Sethambaram, Mariammah (2020)
Job satisfaction is defined as the level of contentment employees feel with their job. This goes beyond their daily duties to cover satisfaction with team members or managers, satisfaction with organizational policies, and the impact of their job on employees’ personal lives. This study had concentrated on factor involving job satisfaction at Money Services Business (MSB). The researcher had analyzed four factors that influencing job satisfaction which are workload, working environment, training and development and knowledge management. A total of 200 questionnaires will be distribute to 200 staffs who are working in MSB sector which will be involved 40 different licensees and 179 branches and Head Quarters. The data will be analyzed by using Statistic Package for Social Science (SPSS).